Assessment of a Thermally Modified Cellulose Acetate Forward‐Osmosis Membrane Using Response Surface Methodology. Issue 9 (12th July 2018) - Zyaie, Javad; Sheikhi, Mohammad; Baniasadi, Javad; Sahebi, Soleyman; Mohammadi, Toraj
Abstract: Cellulose acetate (CA) flat sheet membranes were fabricated and evaluated in a forward‐osmosis process. Effects of CA concentration, coagulation bath temperature, and annealing thermal treatment on both membrane structure and performance were investigated. NaCl rejection of the optimum membrane was determined utilizing a reverse‐osmosis setup based on conductivity measurements. Two validated models were obtained by means of response surface methodology based on Box‐Behnken design. The optimum operating pressure, temperature, and draw solution concentration were assessed as well. Abstract : Forward osmosis (FO) has become an emerging desalination technology but the fabrication of high‐performance and low‐price membranes for FO is still a concern. Cellulose acetate was investigated as starting material for production of flat sheet FO membranes. The performance of such membranes was evaluated for different operational conditions. Two validated models were elaborated.